2023
DOI: 10.1038/s41598-023-30486-2
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Escherichia coli O157:H7 in imported meat products from Saudi Arabian ports in 2017

Abstract: Escherichia coli O157:H7 is a foodborne pathogen, which causes various health conditions in humans, including fatigue, nausea, bloody diarrhoea and in some cases, even death. In 2017, 15.71% of the total imported food products in Saudi Arabia (SA) were meat-based. India and Brazil are two of the top five countries from where SA imports meat. According to the Saudi Food and Drug Authority, in 2017, at least 562, 280, and 50 samples of imported beef, chicken and sheep meat, respectively, were tested for the pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(21 citation statements)
references
References 14 publications
0
21
0
Order By: Relevance
“…Our ndings were similar with a recent study conducted in 2017, by Saudi Food and Drug Authority (SFDA) that reported the presence of E. coli O157:H7 in 6.8% and 2.2% of the examined beef meat samples imported from India and Brazil, respectively. Moreover, the study concluded that the imported meat can serve as a carrier of E. coli O157:H7, which may lead to epidemics throughout regions of Kingdom of Saudi Arabia (Alhadlaq et al 2023).…”
Section: Discussionmentioning
confidence: 98%
“…Our ndings were similar with a recent study conducted in 2017, by Saudi Food and Drug Authority (SFDA) that reported the presence of E. coli O157:H7 in 6.8% and 2.2% of the examined beef meat samples imported from India and Brazil, respectively. Moreover, the study concluded that the imported meat can serve as a carrier of E. coli O157:H7, which may lead to epidemics throughout regions of Kingdom of Saudi Arabia (Alhadlaq et al 2023).…”
Section: Discussionmentioning
confidence: 98%
“…Amongst these, E. coli O157:H7 was detected respectively 6.80% and 2.20% of the tested beef meat samples . During enrichment, samples weighing 25 g selected for enrichment were placed in sterilised sample bags [152]. They were then homogenized with 225 mL of modified tryptone soya broth (mTSB) supplemented with novobiocin to obtain a ratio: mTSB + sample of 1/10 (mass to volume) [152].…”
Section: )mentioning
confidence: 99%
“…During enrichment, samples weighing 25 g selected for enrichment were placed in sterilised sample bags [152]. They were then homogenized with 225 mL of modified tryptone soya broth (mTSB) supplemented with novobiocin to obtain a ratio: mTSB + sample of 1/10 (mass to volume) [152]. The sample bags were massaged by hand and then incubated at 41.5° C for 12-18 h [1-152-167].…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation
“…Since 2000, the global economic cost of zoonotic outbreaks has exceeded USD 10 billion [ 5 ]. Zoonotic strains have caused a huge economic burden worldwide, examples include Listeria monocytogenes ( L. monocytogenes ) [ 6 ], Streptococcus suis ( S. suis ) [ 7 ], Staphylococcus aureus ( S. aureus ) [ 8 ], Salmonella enterica ( S. enterica ) [ 9 ] and Escherichia coli O157:H7 ( E. coli O157:H7 ) [ 10 ]. In 2022, the Ministry of Agriculture of the People’s Republic of China (PRC) confirmed that salmonellosis, swine streptococcosis and listeriosis are important zoonotic diseases [ 11 ].…”
Section: Introductionmentioning
confidence: 99%